Effects of egg laying week on some egg quality characteristics of rock partridges (a. graeca) - Kemal Kırıkçı; Orhan Çetin; Mustafa Garip; Aytekin Günlü (Eurasian Journal of Veterinary Sciences)
Aim: In this study, it was aimed to determine the effects of egglaying week on some egg quality characteristics of rock partridges. Materials and Methods: Quality characteristics of 160 partridge eggs obtained from 34-41 week ages were investigated. 144 rock partridges in 32 week of ages were used as research material. Results: It was determined that the effects of egg-laying week on egg weight, shape index, yolk index, albumen index, egg shell weight, shell thickness, Haugh Unite, membrane weight and albumen weight were found statistically important (P<0.05). The effects of egg-laying week on yolk weight was found not important (P>0.05). Egg weight, shape index and yolk index of partridge eggs has been increased according to egg-laying week (P<0.05). While albumen index, shell membrane weight, shell membrane thickness has been decreased with the egg-laying week (P<0.05). Conclusion: Some internal and external quality characteristics of partridge eggs were determined and also the differences in these characteristics according to egg-laying week were investigated. it can be recommended further investigations should be carried out on the other factors effecting the quality characteristics of partridge eggs.